Pengaruh penerimaan penggunaan e-samsat terhadap kepatuhan perpajakan di Kota Kupang dengan technology acceptance model (TAM) - Benggu, Agape Esa Putra; Damayanti, Theresia Woro (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
Technological developments are currently growing in various fields, one of which is in the field of government. The One-stop Administration Services Office (SAMSAT) is an adaptation of technology applied in the government sector to provide online services to PKB taxpayers. E-Samsat user still shows a low level which is influenced by perceived usefulness and perceived convenience. This study aims to examine the effect of acceptance of the use of E-Samsat on tax compliance in Kupang with the technology acceptance model (TAM). The research population used PKB taxpayers who are registered at the Samsat Office in Kupang. The sampling technique used purposive sampling and 215 respondents were obtained. The results showed that the variables perceived usefulness and perceived convenience has a positive effect on behavioral intention, behavioral intention has a positive effect on E-Samsat acceptance, and E-Samsat acceptance has a positive effect on tax compliance. The perception of usefulness and convenience will increase the taxpayer's intention to use E-Samsat which can then describe the acceptance and compliance of taxation in Kupang.